THE CORRELATION BETWEEN MOTHER’S KNOWLEDGE, EDUCATION AND FAMILY INCOME WITH NUTRITIONAL STATUS OF TODDLER (AGED 1-5 YEARS) - Ika Rena Pratiwi; Ricardi W Alibasjah; Catur Setiya Sulistiyana (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The role of mothers in the growth and development of toddlers is very important. Mothers must know and understand what is needed for that process because this will affect the nutritional status of toddlers. This relates to knowledge, education, and mother’s income which will affect the provision of food intake for infants. Nutritional status of children is still one of the problems in the world. The incidence of malnutrition in the world reached 104 million children and malnutrition is one-third causes of child mortality worldwide. Basic Health Research in 2007, the prevalence of toddler malnutrition in Indonesia was 18.4%, an increase from 2013 to 19.6% and decreased again in 2018 to 17.7% in the year.Aims: To find out the correlation between mothers’ knowledge level, education and family revenue with nutritional status of toddler.Methods: This research used Cross Sectional design, used Accidental sampling techniques. The samples were taken 289 toddlers (1-5 years). The data obtained were analysed using spearman test.Results: Spearman test results showed there is no significant correlation (p> 0.05) between mother’s knowledge level, education and family revenue with nutritional status of toddler.Conclusion: There is no correlation between mother’s knowledge level, education and family revenue with nutritional status of toddler in Kalitanjung Cirebon Health Center. Keywords: Knowledge level, Mother’s education, Revenue, Nutritional status of toddler